Design and performance evaluation of low-voltage/high-current DC - Panov, Y. (IEEE Transactions on power electronics)
The topology selection, design, and performance evaluation of an on-board DC/DC converter, which delivers power from a 48 V input to a 1.2-1.65 V/70 A microprocessor load, are presented. It was shown that the symmetrical half-bridge topology with the current doubler and synchronous rectifiers is a suitable approach for this application. The measured full-load efficiency of a 200 kHz experimental half-bridge converter was higher than 82% in the entire output and input voltage range